Synergistic effect of bladder cancer-specific oncolytic adenovirus in combination with chemotherapy - Li, Shuwen (Oncol Lett, 2017)
Gene therapy with adenoviral early region gene (E1A) may enhance the susceptibility of neoplastic cells to chemotherapy-induced cell death. Our previous study developed a urothelium-specific oncolytic serotype 5 adenovirus (Ad5) with the uroplakin II (UPII) promoter controlling E1A expression. The present study investigated whether this urothelium-specific recombinant adenovirus (Ad5-UPII-E1A) enhanced mitomycin (MMC) and hydroxycamptothecin (HCPT) sensitization and drug-induced apoptosis in bladder cancer cells. The results of the MTT assay revealed that combination therapy, using Ad5-UPII-E1A and MMC or HCPT, synergistically inhibited the viability of bladder cancer cells in a dose- and time-dependent manner when compared with either agent alone. When cells were treated with Ad5-UPII-E1A alone they arrested in the G1 phase, but cell cycle analysis by flow cytometry revealed S phase arrest when treated with combined therapy. Treatment with MMC or HCPT enhanced Ad5-UPII-E1A-induced apoptosis in 5,637 cells, observed by transmission electron microscopy. Western blot analysis revealed that MMC and HCPT enhanced the E1A expression of the Ad5-UPII-E1A vectorin a dose-dependent manner. The present study demonstrated that Ad5-UPII-E1A combined with MMC or HCPT resulted in synergistic cytotoxicity in a process which involved the promotion of apoptosis in bladder cancer cell lines. MMC and HCPT also promoted the oncolytic effect of Ad5-UPII-E1A. Thus, treatment using Ad5-UPII-E1A combined with MMC or HCPT may be an attractive strategy for the sensitization of bladder cancer to chemotherapy.